Microwave-Assisted Preparation of Hierarchical Porous Carbon Aerogels Derived from Food Wastes for Supercapacitors - Zijun Dong; Tong Li; Xinghe Xu; Yi Chen; Jiemei Fu; Shichang Sun (Nanomaterials)
Preparing carbon aerogel in an eco-friendly and inexpensive manner remains a significant challenge. The carbon aerogels derived from food waste (FWCAs) with a three-dimensional connected network structure are successfully synthesized using microwave radiation. The as-prepared FWCA-4 (The KOH/C ratio is 4) has a large specific surface area (1470 m2/g), pore volume (0.634 m3/g), and a high degree of graphitization. Band-like lattice stripes with a spacing of 0.34 nm, corresponding to the graphite plane, are observed. A high specific capacitance of 314 F/g at 1.0 A/g and an excellent capacitance retention (>90% after 10,000 cycles) make the FWCA-4 suitable for high-performance supercapacitor electrode materials. Furthermore, the specific surface area and pore volume of FWCA-4 are larger and the degree of graphitization is higher than in ordinary porous carbon derived from food waste (FWPC). The assembled symmetrical solid capacitor from FWCA-4 exhibits a maximum energy density of approximately 179.9 W/kg in neutral ion electrolytes. Thus, food waste is successfully used to prepare carbon aerogels through a gelation process using microwave radiation. The recycling of waste biomass is achieved, and the results provide insights for the preparation of carbon aerogels using biomass.